Las revistas y el periodismo científico (2021)
The multidisciplinary or general journals published by Colombian universities, such as the Scientific Magazine of the Francisco José de Caldas District University, the Luis Amigó Catholic University Magazine, the Research Magazine of the Quindío University, the National University Magazine or the EAFIT University Magazine, emerged as media that centralized the publication of scientific articles dedicated to exposing the results of research in different disciplines developed by the groups and programs of these institutions. Some maintain that spirit, others disappeared, but for a few years a few, such as the EAFIT University Magazine, have been transformed into popular science publications adopting the practices of scientific journalism.